Automatización De Una Sala De Ordeño Para El Control De Compuertas, Dosificación De Alimento Y Medición De Leche, Caso De Estudio: Espoch-Ecuador - Zaquinaula, Freddy Patricio Ajila; Sánchez-Acosta, Christian; Pacheco-Reinoso, Juan Carlos; Almaguer, Arisdorgan Diéguez (European Scientific Journal, ESJ, 2018)
This paper focuses on the development of an automatic system for a milking room in the Tunshi Experimental Center of the Polytechnic Superior School of Chimborazo, Ecuador. This research uses a theoretical, empirical and statistical methods, and it was carried out using the SCADA system. The proposal was integrated by three subsystems that fulfill specific functions. These functions are: gate control system, feed dosage control system, and milk measurement system. These subsystems use a Programmable Logic Controller (PLC) that is responsible for communicating with devices such as sensors, electrovalves, and pneumatic actuators. The PLC communicates through a process control server (PCS) using a Control Software developed in LabVIEW, which is responsible for the monitoring and controlling the SCADA System. This is done in order to propose a viable option in a bid to increase the competitiveness of the livestock sector.